Detection and impact of sewage pollution on South Kohala's coral reefs, Hawai'i. (March 2023) - Aguiar, Devon K.; Wiegner, Tracy N.; Colbert, Steven L.; Burns, John; Abaya, Leilani; Beets, James; Couch, Courtney; Stewart, Julia; Panelo, Jazmine; Remple, Kristina; Nelson, Craig
Abstract: Sewage pollution from on-site sewage disposal systems and injection wells is impacting coral reefs worldwide. Our study documented the presence and impact of sewage on South Kohala's coral reefs, on Hawai'i Island, through benthic water quality and macroalgal sampling (fecal indicator bacteria, nutrients, δ 15 N macroalgal tissue), NO3 − stable isotope mixing models, water motion measurements, and coral reef surveys. Sewage pollution was moderate on the offshore reef from benthic seeps, and water motion mixed and diluted it across the benthos. These conditions likely contribute to the dominance of turf algae cover, and the severity and prevalence of growth anomalies and algal overgrowth on corals. Use of multiple indicators and studying water motion was necessary to assess sewage pollution and identify environmental drivers associated with impaired coral health conditions. Methods used in this study can be utilized by natural resource managers to identify and reduce anthropogenic stressors to coral reefs. Highlights: Water quality, currents, and benthic surveys assessed coral reef sewage pollution. Sewage pollution was moderate on the coral reefs from benthic seeps. Water motion mixed and diluted sewage across the coral reefs. Sewage presence was associated with coral growth anomalies and algal overgrowth. Multiple tools identified environmental drivers associated with coral reef impairment.